Identification of Weed and Their Potency as Forage - Halim, Halim; Rembon, F. S.; Resman, Resman (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The weeds are secondary vegetation or pioneer plants growing on agricultural land andÂ fallow land. On agriculture, the weed that grows on the cultivation land was considered alwaysharmful and should be eradicated. However, weeds can be managed properly so that it can providevaluable economic benefits, especially for the breeders. The aim of this study was to identify thekinds of weeds that have the potential as forages. The method used in this study are: (a) ModelParticipatory Rapid Appraisal (PRA) means for identifying the kinds of weeds that have the potentialas forages which involves breeders on research location, (b) method of pot culture which is soilsterile (free weed seeds) mixed with cow manure that allegedly contains weed seeds, then grown inseedling trays. The kinds of weeds that grow furthermore be identified by type, species and families.The results of research showed that there are 20 species from broadleaf weeds, 10 species fromgrasses weeds and 2 species from sedges have potential as forages.Key Word: Weed, Forage, Livestock, Breeder, Economic Benefits